Indonesian University Students’ Attitudes and Aspirations Towards ICT in EFL Learning - Dedy Arianto Bannus; Emeral (The Study Program of English Education of Palangka Raya University, 2023)
The Information and Communication Technology (ICT) has been widely used in learning a language and it seems to influence learners’ attitude on learning a language. Therefore, this study is intended to reveal Indonesian University students’ attitudes on the use of ICT in EFL learning. The data were collected from 152 second-year students on English education program who contributed in an online-survey and 4 of them were involved in a semi-structured interview. To obtain the objective, a mixed-methods research design was applied. The result indicated that Indonesian university students have a high positive attitude towards the application of ICT in their EFL learning.